Clinical Characteristics and Outcomes in Multisystemic Inflammatory Syndrome in Children (MIS-C) Associated with COVID-19: A 12-Month Prospective Study - Viorela Gabriela Nitescu; Diana-Andreea Usurelu; Teodora Olsavszky; Ana-Maria Mihalcea; Andra Postelnicu; Ruxandra Florea; Simona Stanca; Iolanda Cristina Vivisenco; Madalina Elena Petran; Maria-Dorina Craciun; Carmen-Daniela Chivu; Alexandru Ulici; et al. (Microorganisms)
Multisystemic inflammatory syndrome in children (MIS-C) is a rare but potentially severe condition that affects multiple organ systems. This study aimed to assess the clinical characteristics and outcomes of patients diagnosed with multisystemic inflammatory syndrome in children (MIS-C) associated with COVID-19. A 12-month prospective study was conducted at the “Grigore Alexandrescu” Clinical Emergency Hospital for Children, Bucharest. This study included children aged 0–18 years who were diagnosed with MIS-C, as defined by the World Health Organization (WHO), the Royal College of Paediatrics and Child Health (RCPCH), and the Centers for Disease Control and Prevention (CDC) criteria. Data on age, gender, clinical and laboratory findings, treatment, and outcomes were analyzed. Follow-up evaluations occurred at one, three, six, nine, and twelve months post-discharge. Among 36 patients (47.3% female, 52.7% male; mean age, 9.9 years), fever and inflammatory syndrome were present in all patients. Other common symptoms included mucocutaneous (63.8%), gastrointestinal (52.7%), cardiac (47.2%), pulmonary (38.8%), and neurological (11.1%) manifestations. At admission, 14/36 were IgM-positive, while 34/36 were IgG-positive. Follow-up revealed sequelae in two patients, including coronary aneurysms and ground-glass pulmonary opacities. Although MIS-C can be severe, most patients had favorable outcomes with proper treatment. Few long-term, organ-specific complications were observed, highlighting the importance of systematic monitoring to ensure full recovery.